Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4014/jmb.1601.01021
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites Production and Plant Growth Promotion by Pseudomonas chlororaphis and P. aurantiaca Strains Isolated from Cactus, Cotton, and Para Grass

Abstract: Fluorescent pseudomonads have been isolated from halophytes, mesophytes, and xerophytes of Pakistan. Among these, eight isolates, GS-1, GS-3, GS-4, GS-6, GS-7, FS-2 (cactus), ARS-38 (cotton), and RP-4 (para grass), showed antifungal activity and were selected for detailed study. Based on biochemical tests and 16S rRNA gene sequences, these were identified as strains of subsp. and . Secondary metabolites of these strains were analyzed by LC-MS. Phenazine-1-carboxylic acid (PCA), 2-hydroxy-phenazine, Cyclic Lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Our study also showed that isolates belonging to Pseudomonas , Paenibacillus, and Bacillus produced antifungal compounds against different fungal pathogens, including Fusarium oxysporum, Fusarium solani, Curvularia sp. Both Pseudomonas and Bacillus have been reported as growth inhibitors for different fungal pathogens and provide protection against a number of plant diseases (Ali et al 2015; Shahid et al 2017; Khan et al 2017). More than one-half of the isolated strains especially members of Paenibacillus, Bacillus, Pseudomonas and Enterobacter , exhibited cellulase, chitinase, amylase, and protease activity, and a large number of PGPR strains ( Pseudomonas , Enterobacter, Rhizobium and Bacillus ) promote plant growth and suppress plant diseases by producing siderophores, hydrolytic enzymes, and HCN (Mehnaz et al 2010; Chen et al 2013; Khan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that isolates belonging to Pseudomonas , Paenibacillus, and Bacillus produced antifungal compounds against different fungal pathogens, including Fusarium oxysporum, Fusarium solani, Curvularia sp. Both Pseudomonas and Bacillus have been reported as growth inhibitors for different fungal pathogens and provide protection against a number of plant diseases (Ali et al 2015; Shahid et al 2017; Khan et al 2017). More than one-half of the isolated strains especially members of Paenibacillus, Bacillus, Pseudomonas and Enterobacter , exhibited cellulase, chitinase, amylase, and protease activity, and a large number of PGPR strains ( Pseudomonas , Enterobacter, Rhizobium and Bacillus ) promote plant growth and suppress plant diseases by producing siderophores, hydrolytic enzymes, and HCN (Mehnaz et al 2010; Chen et al 2013; Khan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…P. aurantiaca strain PB-St2 showed the production of three novel ortho-dialkyl substituted aromatic acids: Lahorenoic acid A, B and C, with limited antibacterial activities. Later on, P. chlororaphis strain RP-4 also exhibited the production of Lahorenoic acid A, indicating the higher biosynthetic capacity of this genus than anticipated previously (Shahid et al 2017). Diketopiperazines (DKPs) constitute the group of cyclodipeptides (CDPs) and are produced by many species of Pseudomonas.…”
Section: Advances In Identification and Characterization Of Secondarymentioning
confidence: 99%
“…aurantiaca gained a lot of attention being prolific producers of antagonistic secondary metabolites. Plant-commensal strains of P. chlororaphis group and their effective role as biocontrol agents distinguished them as microbes with significant effects on agricultural productivity (Al-Hinai et al 2010;Shanmugaiah et al 2010;Shahid et al 2017). To date, 28 genome sequences of strains of P. chlororaphis group are publically available from diverse hosts and have been reported for their effective suppression and inhibition of important plant pathogens.…”
Section: Rising Interest In Pseudomonas Spp Genome Sequencing and Gementioning
confidence: 99%
See 2 more Smart Citations